“Dirva” company - Žukas, Vladas (Knygotyra, 1992)
“Dirva” company which was functioning during 1918–1940 in Kaunas and Marijampolė, belongs to one of the most famous publishing houses of the Republic of Lithuania. Adomas Dundzila and Bronius Sirutis were the founders and owners of it. The company had a publishing house and a printing house in Marijampolė as well as book-shops in Marijampolė and Kaunas and from 1939 in Vilnius. The production of “Dirva” company consists of 546 books. At different periods of time (1931) the commpany was the most efficient publishing house in Lithuania. The main trends of the publishing activities of this publishing house were the following: manuals for schools (24%), children literature (about 15%), fiction (25%). The rest were the publications of this kind: academic, popular-scientific literature, reference books, musical notes, editions of fine art. The original books prevailed over the others, there were published more than one hundred author books by this company. “Dirva” furthered the development of polygraphic and artistic culture of Lithuanian book publishing (the activities of printing house) and the book distribution (book-shops). The proprietors of the company managed to achieve the synthesis of commercial and cultural activities. In July–September 1940 the printing hause (it was estimated in 750000 lits) and book-shops were nationalized.